2003
DOI: 10.1053/rmed.2002.1469
|View full text |Cite
|
Sign up to set email alerts
|

Impairments and prognostic factors for survival in patients with idiopathic pulmonary fibrosis

Abstract: The aim of the present study was to evaluate exercise limiting factors using cardiopulmonary exercise testing (CPET) in patients with idiopathic pulmonary fibrosis (IPF), and to investigate whether these parameters are related to survival after CPET. We evaluated 41 patients with IPF (mean 68.2 years, 27 male) who performed CPET. The exercise capacity in patients with IPF was limited more strongly by gas exchange and/or ventilatory impairments, compared with cardiac impairment. Using univariate analysis, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 16 publications
4
84
1
Order By: Relevance
“…Receiver operating characteristic curve analysis for cut-off points with Ͼ70% sensitivity and Ͼ60% specificity to detect mortality was performed for exercise capacity (peak V O 2 , peak work-rate) and ventilatory efficiency variables (V E /V O 2 nadir, anaerobic threshold V E /V CO 2 , and tidal volume reserve) as was previously demonstrated. 14,15,19,20 Cox regression analysis using a log-rank test was conducted for survival analysis and comparison between significant cut-off points as well as between the exercise training and control groups at the 40-month time point. Hazard ratio for death or lung transplantation using a Wald test was calculated based on variables' cut-off points that were identified as significant in the receiver operating characteristic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Receiver operating characteristic curve analysis for cut-off points with Ͼ70% sensitivity and Ͼ60% specificity to detect mortality was performed for exercise capacity (peak V O 2 , peak work-rate) and ventilatory efficiency variables (V E /V O 2 nadir, anaerobic threshold V E /V CO 2 , and tidal volume reserve) as was previously demonstrated. 14,15,19,20 Cox regression analysis using a log-rank test was conducted for survival analysis and comparison between significant cut-off points as well as between the exercise training and control groups at the 40-month time point. Hazard ratio for death or lung transplantation using a Wald test was calculated based on variables' cut-off points that were identified as significant in the receiver operating characteristic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…12 V E /V O 2 nadir was defined as the lowest value of V E /V O 2 ratio during the exercise. 14,15,19,20 A novel respiratory parameter, tidal volume reserve, which assesses tidal volume response and ventilatory efficiency during exercise, was calculated from CPET; tidal volume reserve was defined as the peak tidal volume minus the resting tidal volume. CPET parameters were compared with normal values proposed by Wasserman 34 and also expressed as percentage predicted.…”
Section: Cpetmentioning
confidence: 99%
See 2 more Smart Citations
“…V9O 2 ,peak and V9E/V9CO 2 A retrospective study of 41 patients with a clinical diagnosis of idiopathic pulmonary fibrosis reported that Pa,O 2 slope, V9O 2 ,peak, O 2 pulse at peak exercise and V9E/V9CO 2 at peak exercise are significant predictors of survival [196]. Interestingly, among the above indices, Pa,O 2 slope was correlated most closely with the survival rate.…”
Section: Interstitial Lung Diseasesmentioning
confidence: 98%